Bombs and ballots governance by Islamist terrorist and guerrilla groups - Wiegand, Krista Eileen (Ashgate Pub., 2010)
Examines the different political strategies that Islamist terrorist and guerrilla groups use to achieve their political objectives. This title contributes to the study of state-society relations in the Middle East, exposing the blurred line between terrorist activity and governance.